Atomic layer deposited TiO2 on a nitrogen-doped graphene/sulfur electrode for high performance lithium–sulfur batteries. Issue 4 (10th March 2016) - Yu, Mingpeng; Ma, Junsheng; Song, Hongquan; Wang, Aiji; Tian, Fuyang; Wang, Yinshu; Qiu, Hong; Wang, Rongming
Abstract : A nitrogen-doped graphene/sulfur composite was further modified with atomic layers of TiO2 and used as the cathode of lithium–sulfur batteries, exhibiting superior cycling stability, good rate capability and high coulombic efficiency. Abstract : Nitrogen-doped graphene (NG) has been fabricated and used as a carbon matrix for sulfur impregnation to construct cathodes for lithium–sulfur (Li–S) batteries. Atomic layers of TiO2 were further deposited on the electrode and the thickness was controlled by adjusting the number of deposition cycles to 0, 5, 20 and 40. The results showed that all the surface modified electrodes demonstrate high capacity, good rate capability, and enhanced cyclability compared to the bare electrode. Specifically, the electrode contained 59% (by weight, wt%) sulfur and with the addition of 20 cycle-TiO2 it demonstrated a superior boost in the active sulfur utilization (discharge capacity: 1374 mA h g −1 at 0.1C). It also delivered initial discharge capacity up to 1069.5 mA h g −1 and 918.3 mA h g −1 after 500 cycles at 1C with an average coulombic efficiency of about 99.7%. Moreover, the capacity retention increased from 42% to 61% from 0.1C to 4C with the addition of 20 cycle-TiO2 . The improved electrochemical performance could be attributed to the on-site TiO2 absorption for polysulfide retention as well as the charge transfer enhancement. Theoretical calculations revealed that TiO2 exhibits a strong binding energy for lithium polysulfide species. These results suggest that the TiO2 modified NG has potential to be used as a cathode for high-performance Li–S batteries.